1987
DOI: 10.2466/pr0.1987.60.2.599
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Attitudes about Nuclear War

Abstract: 913 students from 6 junior and senior high schools in California responded to a 20-item questionnaire using 4-point Likert-type ratings to indicate their 3 greatest worries, to the State-Trait Anxiety Inventory, and nuclear-war-related items. On forced-choice items concerns were parents dying for 53.5%, getting bad grades for 37.0%, and nuclear war for 31.9%; however, the three greatest worries were parents dying for 54.9%, nuclear war for 32.8%, and bad grades for 25.9%. Older adolescents were less worried th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
0
20
0
Order By: Relevance
“…The children and their parents filled out a Children's Worry Scale, which was a modified version of an instrument created to assess adolescents' worries about nuclear war in relation to other life concerns (Doctor et al, 1987). The original instrument had three subscales, determined by factor analysis: Personal/Injury Issues (e.g., "parents dying," "becoming sickhippled," "your own death"); Psychological Issues (e.g., "people not liking you," "looking ugly," "getting bad grades"); and Public Issues (e.g., "nuclear war," "pollution," "world over-population").…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The children and their parents filled out a Children's Worry Scale, which was a modified version of an instrument created to assess adolescents' worries about nuclear war in relation to other life concerns (Doctor et al, 1987). The original instrument had three subscales, determined by factor analysis: Personal/Injury Issues (e.g., "parents dying," "becoming sickhippled," "your own death"); Psychological Issues (e.g., "people not liking you," "looking ugly," "getting bad grades"); and Public Issues (e.g., "nuclear war," "pollution," "world over-population").…”
Section: Methodsmentioning
confidence: 99%
“…By ages 9 to 11 years, children's predominant worries and fears were found to shift away from supernatural or unrealistic concerns (Orton, 1982) and to be related more to school, social acceptance, bodily injury, and global issues (Hamilton, van Mouwerik, Oetting, Beauvais, & Keilin, 1988). with a particular focus in the latter instance on nuclear war (Doctor et al, 1988;Doctor et al, 1987;King et al, 1989). A number of studies have also found a decline in worrying with age (Davidson, White, Smith, & Poppen, 1989;Hamilton et al, 1988;King et al, 1989).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…Although the findings are less consistent regarding developmental trends in types of fears, there is some evidence that younger children are more likely to express fears of animals, imaginary beings, or the unknown, whereas their older counterparts tend to worry more about realistic dangers as well as social evaluation and psychic stress (Bauer, 1976;Gullone & King, 1993;Ollendick et al, 1985). At all developmental levels, however, the most prevalent fears concern danger and death (Doctor, Goldenring, & Powell, 1987;Gullone & King, 1993;Ollendick, Yule, & Oilier, 1991;Spence & McCathie, 1993). These age and gender differences have important implications not only for developmental theories, but also for preventive and clinical interventions.…”
mentioning
confidence: 99%